Advances in clinical chemistry. - Makowski, Gregory S. (Gregory Stephen) (Advances in Clinical Chemistry., 2015)
This volume the latest installment in this internationally acclaimed series. It contains chapters authored by world-renowned clinical laboratory scientists, physicians, and research scientists. The serial discusses the latest and most up-to-date technologies related to the field of clinical chemistry and is the benchmark for novel analytical approaches in the clinical laboratory.